Using estrus detection patches to optimally time insemination improved pregnancy risk in suckled beef cows enrolled in a fixed-time artificial insemination program - Hill, Scott L.; Grieger, David M.; Olson, K.C.; Jaeger, John R.; Dahlen, C. R.; Bridges, G. A.; Dantas, F.; Larson, J. E.; Muth-Spurlock, A. M.; Ahola, J. K.; Fischer, M. C.; Perry, G. A.; et al. (My University, 2017)
A multilocation study examined pregnancy risk (PR) after delaying AI in suckled beef cows from 60 to 75 h when estrus had not been detected by 60 h in response to a 7-d CO-Synch + progesterone insert (CIDR) timed AI (TAI) program (d-7: CIDR insert concurrent with an injection of GnRH; d 0: PGF(2 alpha) injection and removal of CIDR insert; and GnRH injection at TAI [ 60 or 75 h after CIDR removal]). A total of 1,611 suckled beef cows at 15 locations in 9 states (CO, IL, KS, MN, MS, MT, ND, SD, and VA) were enrolled. Before applying the fixed-time AI program, BCS was assessed, and blood samples were collected. Estrus was defined to have occurred when an estrus detection patch was >50% colored (activated). Pregnancy was determined 35 d after AI via transrectal ultrasound. Cows (n = 746) detected in estrus by 60 h (46.3%) after CIDR removal were inseminated and treated with GnRH at AI (Control). Remaining nonestrous cows were allocated within location to 3 treatments on the basis of parity and days postpartum: 1) GnRH injection and AI at 60 h (early-early = EE; n = 292), 2) GnRH injection at 60 h and AI at 75 h (early-delayed = ED; n = 282), or 3) GnRH injection and AI at 75 h (delayed-delayed = DD; n = 291). Control cows had a greater (P < 0.01) PR (64.2%) than other treatments (EE = 41.7%, ED = 52.8%, DD = 50.0%). Use of estrus detection patches to delay AI in cows not in estrus by 60 h after CIDR insert removal (ED and DD treatments) increased (P < 0.05) PR to TAI when compared with cows in the EE treatment. More (P < 0.001) cows that showed estrus by 60 h conceived to AI at 60 h than those not showing estrus (64.2% vs. 48.1%). Approximately half (49.2%) of the cows not in estrus by 60 h had activated patches by 75 h, resulting in a greater (P < 0.05) PR than their nonestrous herd mates in the EE (46.1% vs. 34.5%), ED (64.2% vs. 39.2%), and DD (64.8% vs. 31.5%) treatments, respectively. Overall, cows showing estrus by 75 h (72.7%) had greater (P < 0.001) PR to AI (61.3% vs. 37.9%) than cows not showing estrus. Use of estrus detection patches to allow for a delayed AI in cows not in estrus by 60 h after removal of the CIDR insert improved PR to TAI by optimizing the timing of the AI in those cows.
Citation: Hill, S. L., Grieger, D. M., Olson, K. C., Jaeger, J. R., Dahlen, C. R., Bridges, G. A., . . . Stevenson, J. S. (2016). Using estrus detection patches to optimally time insemination improved pregnancy risk in suckled beef cows enrolled in a fixed-time artificial insemination program. Journal of Animal Science, 94(9), 3703-3710. doi:10.2527/jas2016-0469
Keywords: Beef Cattle; Estrus Detection; Timed Ai; Progesterone Concentrations; Embryonic-Development; Delayed